Demarcações escultóricas: uma abordagem sobre o espaço ocupado e a escultura - Chagas, Roberto Azevedo (2015)
This reflection is the poetic investigation of the contemporary sculptor who works in different sites (traveler) demarcation of these spaces. Thus, this reflection is built in the space of sculpture and public space field, establishing relations with the wider environment punctuated by geography of artist. With the object of research the demarcation of space, replaces the historical issues sculpture form as a means of scoring spaces to reflect on ways to demarcations of certain places and establish relationships that place the time and space of the actions and structures of the artist .